Confirming the Existence of the Kingdom: The Efforts of Territorial Consolidation and Formation of Cultural Identity During the Reign of Hamengku Buwana I, 1755 – 1792 - Sutarwinarmo Sutarwinarmo; Agustinus Supriyono; Dhanang Respati Puguh (Indonesian Historical Studies, 2017)
This article discusses the efforts of territorial Consolidation and formation of cultural identity during the reign of Hamengku Buwana I. This article is written using the historical method and utilizing primary sources in the form of VOC archives stored in the National Archives of the Republic of Indonesia and Java manuscripts stored in Yogyakarta Sultanate, as well as secondary sources in the form of articles and books. After Giyanti Agreement in 1755, Sultan Hamengku Buwana I attempted to consolidate his territory through negotiation, dispute settlement and law enforcement in order to preserve the sovereignty and territorial integrity of his kingdom. He also developed Ringgit Swargen, Yogyakarta style leather puppets that have the different shape from Surakarta style leather puppets developed by Surakarta Sunanate as one of the cultural identity of Yogyakarta Sultanate. The leather puppet show was used to control the areas that were in the territory of the Sultanate of Yogyakarta, as the leather puppet show performed outside the palace must obtain permission from the palace puppet master. The efforts of Sultan Hamengku Buwana I failed, due to the conflict that caused the war destroyed the boundaries and the peace agreement that had been made.